A Study of Retail Islamic Banking: The Relationship between Customer Knowledge and Service Quality - Khairul Firdaus Adrutdin; Azlan Ali; Jimisiah Jaafar; Sallaudin Hassan; Nur Syafiqah A. Rahim (International Journal of Supply Chain Management, 2016)
This paper encompasses on the relationship between customer knowledge function and service quality dimension and the effect on customer satisfaction in the context of Malaysian retail Islamic banking. As one of the challenges faced by retail Islamic banking is the customer satisfaction where the level of services rendered and knowledgeable front liners are the concerns, retail Islamic banking needs to improve on their quality of customer services and its measurement should consist of interaction quality and outcome quality. The issues of lack of customer knowledge, awareness and information on retail Islamic banking could be the resulted from the low interaction and outcome of the quality of knowledge supply. Meanwhile, distinctive attention is actually required from the Islamic banking staff due to the complexity of retail Islamic banking products. The customer knowledge function in retail Islamic banking itself should be therefore emphasized alongside with the service quality dimension in order to ensure that the supply of knowledge to the customer will in turn help to increase the customer satisfaction.